Microcomputer data management in an introductory physics laboratory - Chonacky, N. (American Journal of Physics, 1982)
A microcomputer/mini-floppy disk system is used by students in the laboratory portion of an introductory physics course for science majors. Its purposes are to store their experimental data, do data analyses, and exchange messages with the lab instructor. The system also provides computer-assisted instruction (CAI) simulations of certain lab experiments, and interfaces with measuring equipment in certain experiments. Each student has a personal diskette for data files and basic utility programs for an entire semester. The ease of disk data manipulation under program control is exploited in the following ways: (i) a wide variety of data reduction techniques are introduced that permit quantitative comparisons between experimental results and theoretical expectations; (ii) facile data reduction and analyses permit preliminary processing of experimental data during the course of the lab period, so that decisions can be made by students concerning the course of the remainder of the experiment; (iii) accumulated data from various experiments become a course database permitting subsequent analyses of old data adapted in several different logical ways (e.g., RC curcuit data first treated as energy storage, later as one of a number of exponential relationships); (iv) comprehensive course database formed by merging regarding the reliability of experiments. These considerations favor laboratory goals different from the demonstration and confirmation of given physical laws. Specifically they inculcate critical thinking and hypothetico-deductive reasoning. I discuss several very real problem areas that plagued this novice and compromised implementation. I compare these problems with the qualitative improvements in laboratory learning. © 1982, American Association of Physics Teachers. All rights reserved.
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy